SEMIOTIK ANALISIS SEMIOTIK DALAM FILM NGERI-NGERI SEDAP KARYA BENE DION RAJAGUKGUK: ANALISIS SEMIOTIK DALAM FILM NGERI-NGERI SEDAP KARYA BENE DION RAJAGUKGUK - Sihite, Meliyana (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to describe the semiotics contained in the film Ngeri-Ngeri Sedap by Bene Dion Rajagukguk. This research uses a qualitative descriptive research method. The subject of this research is the film Ngeri-Ngeri Sedap by Bene Dion Rajagukguk, with the object of research being the meaning of the signs in the speech contained in the film Ngeri-Ngeri Sedap by Bene Dion Rajagukguk. Data was collected by listening and taking notes, using instruments in the form of notes. The data analysis stage includes data reduction, data presentation, and conclusions. The results of the research show that there are types of semiotics consisting of icon semiotics, which include place icons, trait icons, situation icons, feeling icons, expression icons, then there is index semiotics, there are data that have a cause and effect relationship, and finally there is symbol semiotics.